Prawne granice reklamy w świetle ustawy o zwalczaniu nieuczciwej konkurencji - Więckowski, Kamil (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The importance of advertising in today’s economy tends to increase. This fact is mainly caused by the development of technology, wider range of products offered in the market as well as, to a considerable extent, by the market internalization. The aforementioned factors become the reasons for more severe competition and at the same time make the businessmen find new, more effective methods of promotion. It may lead to reaching for dangerous, from the point of view of the competitive markets and their members, ways of persuasion. That is why it is so important to establish (and effectively exercise) certain laws which would limit (minimalize) the use of such undesirable practices. This paper presents an analysis of the regulation existing in the Polish law and concerning the previously mentioned problems, which is known as the Unfair Competition Act. Certain examples of unfair competition in advertising are characterised in this paper in reference to the content of the act, especially to the works of doctrine and judicature, and because of that it is possible to define legal limitations of the advertising
Keywords: reklama; zakazana reklama; nieuczciwa reklama; nieuczciwa konkurencja; reklama wprowadzająca w błąd; lokowanie produktu